Theoretical criteria in and for diversity that underpin continuous teacher training in chilean early Childhood Education (Revista Electrónica Calidad en la Educación Superior, 2022)
Education in Chile calls for a look at diversity, understanding it through categories, variety and distinction. Thus, continuous training has given rise to the need to formulate theoretical criteria regarding Early Childhood Education in and for diversity. The methodology of this study adopted a qualitative approach of the interpretative-participatory field type, with the support of Grounded Theory and its Continuous Comparative Method. The techniques used were in-depth interviews, and participant observation. The key informants were five educators with more than five years of work experience in early childhood education in the Region of Los Lagos, Chile. The findings were obtained from the interpretation of the empirical situations. In this way, dialectics and actions of the educators were clarified, with information about knowledge and experiences orientated towards diversity. It is concluded that the theoretical criteria will allow the teacher training to be successful, in order to develop competences to achieve the attention of diversity.
Keywords: Theoretical Criteria; Ongoing Teacher Training; Early Childhood Education; Diversity